English: Bahasa Indonesia - Ira Prima Sari; Fitri April Yanti; Dian Imam Saefullah; Bagus Tri Yunianto (Journal of Sustainability Science and Technology, 2021)
Borax is a chemical substance that is prohibited from being used as a food additive because of its toxic nature. However, the use of borax is still widely found, one of which is meatballs the most. This study aims to identify the borax content in meatballs. Samples were taken from Ciroyom Market, Bandung City, Indonesia using total sampling and obtained as many as 10 samples of meatballs. The samples were analyzed qualitatively by observing physical conditions and testing using BaCl2 solution. Meanwhile, quantitative analysis was carried out using a UV-Vis spectrophotometer at a wavelength of 428 nm. The results of the analysis showed that all samples were indicated to contain borax. Even the quantitative test using UV-Vis spectrophotometer showed that the highest borax content was found in sample 10, which was 3.672,9 µg/ml.